Nepal Pediatric Society Guidelines for the Safe Transport of Critically Ill Children in Nepal - Amatya, Puja; Shrestha, Dhruba; Joshi, Suchita; Sharma, Arun; Shrestha, Shrijana; Basnet, Sangita (Journal of Nepal Paediatric Society, 2021)
Transport of critically ill children is associated with increased risk of morbidity and mortality in developing countries due to the lack of adequate resources and skilled personnel. Transport of the sick child remains a major challenge in Nepal as well. The main objective of this article is to describe the importance of safe transport, and be a resource and guide for health care personnel during inter-facility transport of sick children in Nepal. This guideline is based on consensus statement of Nepal Pediatric Critical Care Working Group (NPCCWG) under the aegis of the Nepal Pediatric Society (NEPAS). It includes different components of transport, namely essential equipment, patient preparation, communications, medications, and transport checklist, that are required during transport of sick children, taking into consideration the current resources available in our health care facilities.